2013
DOI: 10.1007/s00484-013-0655-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of heat waves on children’s health: a systematic review

Abstract: Young children are thought to be particularly sensitive to heat waves, but relatively less research attention has been paid to this field to date. A systematic review was conducted to elucidate the relationship between heat waves and children's health. Literature published up to August 2012 were identified using the following MeSH terms and keywords: "heatwave", "heat wave", "child health", "morbidity", "hospital admission", "emergency department visit", "family practice", "primary health care", "death" and "m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(88 citation statements)
references
References 46 publications
5
72
0
6
Order By: Relevance
“…In contrast, the lowest risk for HRI in the ED was seen among infants and children. Children have not been consistently identified as a vulnerable demographic, suggesting that very particular risk factors and circumstances must be present [31].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the lowest risk for HRI in the ED was seen among infants and children. Children have not been consistently identified as a vulnerable demographic, suggesting that very particular risk factors and circumstances must be present [31].…”
Section: Discussionmentioning
confidence: 99%
“…The ideal way of handling extreme temperatures is through primary prevention —for example, health education 64. A heat early warning system can be of great use, especially for those parents whose children have a history of chronic lower respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is comparatively less information regarding heat health effects in children, partially due to the fact that population-based data are sometimes restricted to elderly populations by nature (e.g., mortality, cardiovascular outcomes) or by source (e.g., Medicare data on hospitalizations). Children may also have higher susceptibility to adverse health impacts from heat, particularly in relation to morbidity rather than mortality (Bartlett, 2008; Ebi and Paulson, 2007; Kravchenko et al, 2013; Sheffield and Landrigan, 2011; Xu et al, 2012; Xu et al, 2014). Several studies conducted outside the US have found associations between high temperatures or heat waves and various measures of morbidity among children (Checkley et al, 2000; Chou et al, 2010; Hashizume et al, 2007; Kovats et al, 2004; Lam, 2007; Leonardi et al, 2006; Nitschke et al, 2011; Onozuka and Hashizume, 2011; Pudpong and Hajat, 2011; Xu et al, 2012; Xu et al, 2013; Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Children may also have higher susceptibility to adverse health impacts from heat, particularly in relation to morbidity rather than mortality (Bartlett, 2008; Ebi and Paulson, 2007; Kravchenko et al, 2013; Sheffield and Landrigan, 2011; Xu et al, 2012; Xu et al, 2014). Several studies conducted outside the US have found associations between high temperatures or heat waves and various measures of morbidity among children (Checkley et al, 2000; Chou et al, 2010; Hashizume et al, 2007; Kovats et al, 2004; Lam, 2007; Leonardi et al, 2006; Nitschke et al, 2011; Onozuka and Hashizume, 2011; Pudpong and Hajat, 2011; Xu et al, 2012; Xu et al, 2013; Xu et al, 2014). In the US, assessment of age-stratified associations between ambient temperature and morbidity with evaluation of effects across the full age range, including children, has been conducted with limited geographic coverage (Basu et al, 2012; Fletcher et al, 2012; Green et al, 2010; Lin et al, 2009; Li et al, 2012; Lippmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%